2016
DOI: 10.1007/s11892-016-0817-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Group Medical Visits With Those Who Have Diabetes: Examining the Evidence

Abstract: The number of people with diabetes is expected to rise to over 592 million by the year 2035. Past work provides evidence that the conventional method of primary care delivery may not meet many patients' needs. An alternative to the conventional one-on-one appointment is care offered to a group of patients through group medical visits (GMVs). Group medical visits for diabetes have a positive impact on physiologic and self-care outcomes including improved HbA1c, blood pressure control and self-management skills.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…More work is needed to examine the use of NP‐led GMVs in other Canadian provinces and jurisdictions. While this study examines the interprofessional processes that can unfold within a GMV, other work has shown that GMVs can positively affect clinical outcomes such as HbA1C and blood pressure, for patients with diabetes . Although some studies have examined GMVs for heart disease, chronic obstructive pulmonary disease (COPD), dementia and mental illness, much of the current work has focused on GMVs for diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed to examine the use of NP‐led GMVs in other Canadian provinces and jurisdictions. While this study examines the interprofessional processes that can unfold within a GMV, other work has shown that GMVs can positively affect clinical outcomes such as HbA1C and blood pressure, for patients with diabetes . Although some studies have examined GMVs for heart disease, chronic obstructive pulmonary disease (COPD), dementia and mental illness, much of the current work has focused on GMVs for diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is limited by time and a moderate sample size that is majority female, although most diabetes group visit investigations are less than a year, have high attrition, and are minority male. 6,[10][11][12] Results are also limited to Spanishspeaking individuals at a nonprofit clinic. Though multifaceted interventions limit deciphering the most efficacious variable, these strategies have been found valuable for the complicated nature of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Group visits or shared medical appointments are a cost-effective intervention, comprising of education, integrated primary care (e.g., medication reconciliation), and goal development. [9][10][11] Most group visits are led by physicians or other health professionals 12 and, though bilingual providers add value in relating to the patient population, they are in short supply. 13 Integrating CHWs into group visits has showed value in overcoming cultural and language barriers.…”
Section: Introductionmentioning
confidence: 99%
“…This is notable given that these and other chronic conditions disproportionately affect low-income individuals, and health care disparities exacerbate this higher prevalence. There is a strong research base for diabetes GMVs, 11,40 and integrative care may provide additional benefits to patients with diabetes. All authors of this article have ongoing qualitative and mixed-methods projects examining group-based integrative care for chronic pain.…”
Section: Discussionmentioning
confidence: 99%